Analisis Manajemen Hotel Syariah Yasmin Hotel and Restaurant di Kabupaten Bangka Barat (Tinjauan Fatwa DSN Mui No: 108/DSN-Mui/X/2016) - Faldini, Mandala (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2018)
This study aims to determine the implementation of Yasmin and Restaurant management in accordance with the National Sharia Council (DSN) Indonesian Ulema Council (MUI) Fatwa No. 108 / DSN-MUI / X / 2016 concerning Islamic hotels. This research is a qualitative research with a descriptive exploratory approach. The method used is an in-depth interview with the Manager of the Yasmin Hotel and Restaurant, accompanied by observation and documentation. The data analysis technique used is the James Spardley model of data analysis techniques through four stages, namely: Domain Analysis, Taxonomic Analysis, Componential Analysis, Cultural Theme Analysis. The results of this study indicate that the implementation of Yasmin hotel and restaurant management in West Bangka Regency is in accordance with the MUI DSN fatwa No: 108 / DSN-MUI / X / 2016.